THE NEW PROCESSING METHOD OF QUASI-PERIODIC PULSE SIGNALS USING WAVELET ANALYSIS AND HERMIT TRANSFORM - Dmitry Balakin; Eduard Trunov; Vitaly Shrykov (Proceedings on Engineering Sciences, 2023)
The article considers the basic principles of constructing a method for processing quasi-periodic pulse signals. The method is based on the combined use of wavelet analysis and the Hermite transform, in particular, the Gauss-Hermite function. Wavelet transform is considered as a cross-correlation function. The Gauss-Hermite functions are used as a basis in the wavelet analysis. Approbation of the method is carried out as on a test signal, in the form of a rectangular pulse with additive noise, which at some point in time has a local inhomogeneity, also on the real signal received from the bearings of the gas turbine engine.